CENTRAL ASIA AS A SECURITY COMPLEX: THEORY AND PRACTICE - BOBOKULOV, Inomjon (CENTRAL ASIA AND THE CAUCASUS, 2012)
The academic community is aware of three hypostases of Central Asia: (1) a geographical region; (2) a political entity; and (3) a civilizational expanse—each with its own limits. As a geographical region, Central Asia is limited by “natural borders” (mountains, rivers, the steppe, and the sea); as a political entity, it is contained within the state borders of the new political units; and as a civilizational expanse, it is described as the local peoples’ cultural and/or ethnolinguistic community, that is, by civilizational factors. The idea of Central Asia as the space in which four post-Soviet Central Asian republics and Kazakhstan are situated is the region’s most frequently used, not to say dominating, political description. Central Asia as a political entity is a target of academic studies in its own right and an inalienable part of the foreign policy strategies of the key members of the international community.